Analytical solution of the problem of thermoelasticity for a plate heated by a source with a constant heat supply on one surface - et. al., N.A. Kucheva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An analytical solution to the problem of thermoelasticity for a plate heated by a source with a constant heat supply on one surface is proposed. Numerous comparisons of the results obtained on the basis of the analytical solution with the numerical one are carried out. When comparing the analytical and numerical solutions, it is shown that the advantage of the analytical solution is that it allows you to determine the highest stress values in the entire heating time range, while using the numerical method, it is necessary to carry out a large number of calculations at fixed times. However, the finite element method makes it possible to determine the stresses in the areas of the slab far from its center, where the analytical solution turns out to be not valid.